Stress, epigenetics and depression: A systematic review. (July 2019) - Park, Caroline; Rosenblat, Joshua D.; Brietzke, Elisa; Pan, Zihang; Lee, Yena; Cao, Bing; Zuckerman, Hannah; Kalantarova, Anastasia; McIntyre, Roger S.
Highlights: Childhood maltreatment is an important stressor associated with stress & depression. Stress- and depression-associated changes were mostly found in NRC31 and SLCA4 . Epigenetic changes occurring at different loci may have variable downstream effects. Most studies measured epigenetic changes using peripheral tissue samples. Future studies should evaluate epigenetic effects of psychotropic medication use. Abstract: Environmental stressors, such as childhood maltreatment, have been recognized to contribute to the development of depression. Growing evidence suggests that epigenetic changes are a key mechanism by which stressors interact with the genome leading to stable changes in DNA structure, gene expression, and behaviour. The current review aimed to evaluate the relationship between stress-associated epigenetic changes and depression. Human studies were identified via systematic searching of PubMed/Medline from inception to February 2018. Seventeen articles were identified. Stress-associated epigenetic changes in the following genes were correlated with depression: NRC31, SLCA4, BDNF, FKBP5, SKA2, OXTR, LINGO3, POU3F1 and ITGB1 . Epigenetic changes in glucocorticoid signaling (e.g., NR3C1, FKBP5 ), serotonergic signaling (e.g. SLC6A4 ), and neurotrophin (e.g., BDNF ) genes appear to be the most promising therapeutic targets for future research. However, continued research is warranted due to inconsistent findings regarding the directionality of epigenetic modification. Future studies should also aim to control for the use of psychotropic agents due to their widespread use in depressed populations and established effects on DNA methylation.